Instilling Communication Skill Through A Cultural Literacy - HANUR, BINTI SUAIDAH (JOSAR (Journal of Students Academic Research), 2024)
Children born in the 21st century are required to be critical-minded, creative, communicative and able to collaborate because the 21st century is a digital century where everything uses technology and information systems. This requires parents to be media literate to keep up with the times but unfortunately not all parents are media literate which results in not all children being able to develop abilities according to the needs of this digital century. This article tries to review the relationship between the cultivation of literacy culture and the development of children's communication skills taken from the results of a case study of one of the students in the Playgroup class of PAUD Kuncup Melati Pandan Badas Kediri.